Mechanical validation of balanced cross-sections: The case of the Mont Terri anticline at the Jura front (NW Switzerland). (June 2015) - Caër, Typhaine; Maillot, Bertrand; Souloumiac, Pauline; Leturmy, Pascale; Frizon de Lamotte, Dominique; Nussbaum, Christophe
Abstract: Close to north-west front of the Jura thrust belt in Switzerland, the Mont Terri anticline is located at a disruption of the Muschelkalk decollement, due to a former normal fault. Numerous geological data are available thanks to a motorway tunnel cross-cutting the fold and an underground laboratory. Original field data, two geological maps, a borehole, and a highway tunnel constrain the inner structure. The anticline is characterized by an overturned frontal limb, a steep back limb, and a ramp cross-cutting older normal faults. Three geological cross-sections and three 2D kinematic models are proposed as various combinations of fault-bend folding, fault-propagation folding and detachment folding. The main motivation of this study is to illustrate how geometrical constructions can be constrained by the kinematic approach of limit analysis, which determines the optimal deformation, including faults, that verifies mechanical equilibrium and the Coulomb criterion. Matching some of the important kinematic steps assumed in each three interpretations to the optimal deformation leads us to define the compatible ranges of values of the frictional parameters. These ranges allow us to assess the likeliness of the important kinematic steps of each kinematic model. The present analysis provides a quantitative link between the assumed evolution of the internal structure, and the concomitant evolutions of the topography and of the frictional parameters. Highlights: Two new cross sections and kinematics of the Mont Terri anticline are proposed. We use the limit analysis theory to evaluate each proposition. Mechanical parameter values are associated to each proposed kinematics. Erosion/topography is a primordial factor, difficult to estimate through time.